2002
DOI: 10.1111/j.1444-0938.2002.tb03032.x
|View full text |Cite
|
Sign up to set email alerts
|

The ocular response to extended wear of a high Dk silicone hydrogel contact lens

Abstract: Purpose: A four-month extended wear clinical trial was conducted to compare the ocular effects of a high Dk Balafilcon A silicone hydrogel lens and a low Dk HEMA 38.6 per cent H, O soft lens. Method Twenty-four subjects who were adapted to daily wear of soft lenses wore a high Dk lens in one eye and a low Dk HEMA lens in the other eye for four months on an extended wear basis after one week of daily wear. Thirteen progress evaluations were conducted using standard clinical procedures.Results: Eighteen subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 22 publications
2
39
0
2
Order By: Relevance
“…Numerous authors [10][11][12] have reported that silicone-hydrogel lenses worn on an extended wear basis induced significantly lower grades of conjunctival redness compared to those observed with hydrogel extended wear lenses. Morgan and Efron 13 also demonstrated that silicone-hydrogel lenses worn on an extended wear basis induce relatively low grades of conjunctival redness (between 0.4 and 0.6).…”
Section: Prevalencementioning
confidence: 88%
See 1 more Smart Citation
“…Numerous authors [10][11][12] have reported that silicone-hydrogel lenses worn on an extended wear basis induced significantly lower grades of conjunctival redness compared to those observed with hydrogel extended wear lenses. Morgan and Efron 13 also demonstrated that silicone-hydrogel lenses worn on an extended wear basis induce relatively low grades of conjunctival redness (between 0.4 and 0.6).…”
Section: Prevalencementioning
confidence: 88%
“…As discussed above, silicone hydrogel lenses induce minimal amounts of conjunctival redness. [10][11][12] Alteration to care systems…”
Section: Prognosismentioning
confidence: 99%
“…Grant et al 9 reported that the incidence of CLPC in patients wearing rigid lenses on an extended wear basis was 2%, versus 6-12% for hydrogel disposable extended wear. Fonn et al 15 reported the results of a 4-month clinical trial in which six out of 18 patients (33%) wearing silicone hydrogel lenses on an extended wear basis developed CLPC; two of these patients were discontinued from the study because of the severity of the condition.…”
Section: H a P T E R 1mentioning
confidence: 98%
“…Thus, they protect the cornea from the hypoxia caused changes. [11][12][13][14] Furthermore, Santos et al have proven that SiH contact lenses are generally less susceptible to microbial adhesion, in comparison to conventional hydrogels. This feature facilitates better lens resistance to bacteria.…”
Section: Discussionmentioning
confidence: 99%